A Rare Case of Congenital Adrenal Hyperplasia with Giant Adrenal Myelolipoma - Longoria-Dubocq, Texell; Torres-Aguiar, Roberto; Ruiz-Vega, Karla; De Ayala-Hillmann, Rafael; Lopez-Enriquez, Reynold (Puerto Rico Health Sciences Journal, 2020)
Adrenal incidentalomas are tumors located in the adrenal glands and found on imaging done for purposes not related to adrenal disease. In other cases adrenal mases can be radiologically found when an adrenal hormone secreting tumor is suspected, such as a pheochromocytoma or Cushing’s diseases. Adrenal incidentalomas may be classified as functional or non-functional based on whether they produce hormones, such as aldosterone, cortisol, and androgens, or catecholamines. Studies indicate that around 8% of adrenal incidentalomas are adrenal gland myelolipomas (AGMs). AGMs are non-malignant masses that can cause the compression of vital organs and vessels if said masses become large enough. In patients with congenital adrenal hyperplasia (CAH), adrenocorticotropic hormone (ACTH) levels tend to be elevated due to the lack of adrenal-hormone production. Patients with CAHs are treated with steroids that suppress ACTH levels and prevent adrenal gland hyperplasia. Around 10% of AGMs are found in untreated CAHs. Our patient was a 36-year-old male who was on steroids due to CAH and intermittent abdominal pain; a CT scan revealed a large left adrenal mass that was displacing organs towards the right. Pathological analysis revealed an AGM exceeding 30 x 23.6 x 16.7 cm. This AGM is one of the largest ever to be reported in the literature.